2017
DOI: 10.1080/21505594.2017.1356537
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of 3 different resistance plasmids in a multi-drug resistant Cronobacter sakazakii isolate causing neonatal infections

Abstract: Cronobacter sakazakii 505108 was isolated from a sputum specimen of a neonate with severe pneumonia. C. sakazakii 505108 co-harbors 3 resistance plasmids of the IncHI2, IncX3, and IncFIB incomparability groups, respectively. These 3 plasmids have acquired several accessory modules, which carry an extremely large number of resistance genes, especially including those involved in resistance to carbapenems, aminoglycoside, tetracyclines, and phenicols and sulphonamide/trimethoprim. These plasmid-borne antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…In contrast, CFSAN’s Galaxy’s AMRFinderPlus tool correctly identified all antimicrobial resistence/tolerance genes present on p505108-MDR (KY978628) which included the following antimicrobial resistance/tolerance genes: bla TEM– 1 , dfrA19, aph(3′′)-Ib, aph(6)-Id, mcr-9.1, aph(3′)-Ia, catA2, tet(D), aac(6′)-Ib3, bla SHV– 12 , sul1, bla DHA– 1 , qnrB4, qacEdelta1, arr, aac(3)-II, and aac(6′)-IIc with predicted resistances/tolerances to β-Lactam based compounds, Trimethoprim, Aminoglycoside, Colistin, Phenicol, Tetracycline, Sulfonamide, Quinolone, Quaternary Ammonium, and Rifamycin antibiotics, respectively. The antimicrobial resistance genes found on plasmid p505108-NDM (KY978629) were identified as ble, bla NDM– 1 , and bla SHV– 12 with predicted resistances to bleomycin and NDM-1 β-Lactam antibiotics, consistent with previously results reported by Shi et al (2018) .…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast, CFSAN’s Galaxy’s AMRFinderPlus tool correctly identified all antimicrobial resistence/tolerance genes present on p505108-MDR (KY978628) which included the following antimicrobial resistance/tolerance genes: bla TEM– 1 , dfrA19, aph(3′′)-Ib, aph(6)-Id, mcr-9.1, aph(3′)-Ia, catA2, tet(D), aac(6′)-Ib3, bla SHV– 12 , sul1, bla DHA– 1 , qnrB4, qacEdelta1, arr, aac(3)-II, and aac(6′)-IIc with predicted resistances/tolerances to β-Lactam based compounds, Trimethoprim, Aminoglycoside, Colistin, Phenicol, Tetracycline, Sulfonamide, Quinolone, Quaternary Ammonium, and Rifamycin antibiotics, respectively. The antimicrobial resistance genes found on plasmid p505108-NDM (KY978629) were identified as ble, bla NDM– 1 , and bla SHV– 12 with predicted resistances to bleomycin and NDM-1 β-Lactam antibiotics, consistent with previously results reported by Shi et al (2018) .…”
Section: Resultssupporting
confidence: 88%
“…, arr, aac(3)-II, and aac(6 )-IIc with predicted resistances/tolerances to β-Lactam based compounds, Trimethoprim, Aminoglycoside, Colistin, Phenicol, Tetracycline, Sulfonamide, Quinolone, Quaternary Ammonium, and Rifamycin antibiotics, respectively. The antimicrobial resistance genes found on plasmid p505108-NDM (KY978629) were identified as ble, bla NDM−1 , and bla SHV−12 with predicted resistances to bleomycin and NDM-1 β-Lactam antibiotics, consistent with previously results reported by Shi et al (2018).…”
Section: Identification and Amr Characterization Of Cronobacter Specisupporting
confidence: 88%
See 2 more Smart Citations
“…By performing plasmid multilocus sequence typing ( https://pubmlst.org/bigsdb?db=pubmlst_plasmid_seqdef&page=sequenceQuery ), we determined that pGW1 is IncHI2-ST1 and is mainly found in other countries ( 9 ). Full-plasmid comparison revealed that pGW1 is closely related to p505108-MDR ( 5 ).…”
mentioning
confidence: 99%